2004
DOI: 10.1126/science.1102068
|View full text |Cite
|
Sign up to set email alerts
|

The Kondo Effect in the Presence of Ferromagnetism

Abstract: We measured Kondo-assisted tunneling via C60 molecules in contact with ferromagnetic nickel electrodes. Kondo correlations persisted despite the presence of ferromagnetism, but the Kondo peak in the differential conductance was split by an amount that decreased (even to zero) as the moments in the two electrodes were turned from parallel to antiparallel alignment. The splitting is too large to be explained by a local magnetic field. However, the voltage, temperature, and magnetic field dependence of the signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
571
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 530 publications
(615 citation statements)
references
References 21 publications
29
571
1
Order By: Relevance
“…The splitting in both configurations also occurs when both magnetic electrodes are of the same material, but the corresponding coupling strengths to the dot are different. Indeed, such a splitting in parallel and also antiparallel configurations was recently observed experimentally [25]. When similar electrodes are symmetrically coupled to the dot, the splitting occurs only in the parallel configuration.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The splitting in both configurations also occurs when both magnetic electrodes are of the same material, but the corresponding coupling strengths to the dot are different. Indeed, such a splitting in parallel and also antiparallel configurations was recently observed experimentally [25]. When similar electrodes are symmetrically coupled to the dot, the splitting occurs only in the parallel configuration.…”
Section: Discussionmentioning
confidence: 56%
“…The Kondo anomaly survives then in the antiparallel magnetic configuration and is significantly suppressed in the parallel one. Recent experimental observations on C 60 molecules attached to ferromagnetic (Ni) electrodes support these general theoretical predictions [25].…”
Section: Introductionmentioning
confidence: 67%
“…29,31,35 In the presence of ferromagnetism, the Kondo resonance therefore splits apart as confirmed experimentally. 32,37 While such a splitting is well understood, the impact of a nonequilibrium spin current on the Kondo resonance has so far been little addressed in correlated nanostructures. This remains an open question since a decade ago it was shown that a spin current flowing from a Co wire through a Cu(Fe) wire is able to strongly suppress the resistivity of the Cu(Fe) Kondo alloy near the interface.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] It has also been successfully evidenced in nanoscale devices, [17][18][19][20][21] in particular quantum dots, [17][18][19][22][23][24] carbon nanotubes, [25][26][27] and nanowires. 28 Of particular interest-especially in the context of spintronics, is the issue of screening in the presence of a magnetic environment such as spin-polarized electrodes [29][30][31][32][33][34][35] and spinpolarized edge states. 36 A spin-dependent hybridization for the spin-up and spin-down energy levels of the impurity is then predicted, resulting in an effective static magnetic field at the impurity site (this field can eventually be compensated by an external magnetic field).…”
Section: Introductionmentioning
confidence: 99%
“…The zero-bias anomaly of the cotunneling current is therefore distinctively different from that associated with the Kondo effect. The latter occurs at low temperature, T T K , shows up in the parallel configuration as well [9,10], grows logarithmically with decreasing temperature, and reaches perfect transmission, g = 1. Its width at low temperature saturates at k B T K , and it has a different magnetic-field dependence.…”
mentioning
confidence: 99%